2004
DOI: 10.1002/ppap.200400028
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal Plasma Processing for Air‐Pollution Control: A Historical Review, Current Issues, and Future Prospects

Abstract: Summary: This review describes the historical development, current status, and future prospects for nonthermal plasma (NTP) technology and its application as an air‐pollution control. In particular, this review focuses on the cutting‐edge technology of hybrid NTP, where it is combined with other methods such as wet processing, the use of adsorbents, and catalysis. Historical landmarks in the development of NTP technology and the current status of large‐scale applications are discussed. The general characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
366
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 615 publications
(374 citation statements)
references
References 167 publications
0
366
0
1
Order By: Relevance
“…Briefly, the primary ions produced by positive corona discharge in air (e.g., N 2 ϩ• and O 2 ϩ• ) are not detected because they are quantitatively converted via highly efficient exothermic ion/molecule reactions into hydrates of the hydronium ion, H 3 O ϩ (H 2 O) n , which are the major "background" positive ions. The cluster size distribution depends on the APCI source temperature and on the amount of residual humidity in the apparatus: typically at 30°C and at low values of V cone complexes with n ϭ 2, 3, and 4 are detected, the most abundant being usually H 3 O ϩ (H 2 O) 3 . Other ions observed, although in lower abundance, are the hydrates NO ϩ (H 2 O) n , with n ϭ 1-3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the primary ions produced by positive corona discharge in air (e.g., N 2 ϩ• and O 2 ϩ• ) are not detected because they are quantitatively converted via highly efficient exothermic ion/molecule reactions into hydrates of the hydronium ion, H 3 O ϩ (H 2 O) n , which are the major "background" positive ions. The cluster size distribution depends on the APCI source temperature and on the amount of residual humidity in the apparatus: typically at 30°C and at low values of V cone complexes with n ϭ 2, 3, and 4 are detected, the most abundant being usually H 3 O ϩ (H 2 O) 3 . Other ions observed, although in lower abundance, are the hydrates NO ϩ (H 2 O) n , with n ϭ 1-3.…”
Section: Resultsmentioning
confidence: 99%
“…Research and development are very active in this latter field, which comprises not only air [2,3] but, more recently, also water treatment processes [4]. For air pollution control, different types of reactors and power supplies are being developed and tested for production of nonthermal plasmas by means of electrical discharges [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,6 Additional features such as easy operation, moderate capital cost, and simple scalability have led to extensive research on packed bed DBDs. 7 Several studies which have used packing material in conjunction with plasma in a DBD have found enhanced performance in comparison to a plasma alone system; 2,3,6,[8][9][10][11][12] however, many studies have also reported a negative impact on the performance. 9,[13][14][15] This unfavorable response has been shown to be related to packing configuration and the void fraction of the discharge in the packed bed DBD.…”
mentioning
confidence: 99%
“…The most important species utilized for the removal of gaseous pollutants in water containing air are radicals (e.g., O, OH, HO 2 ) and ozone (O 3 ) with different oxidation potentials. A detailed discussion of plasma chemical processes can be found in (Fridman 2008) and, especially for pollutants decomposition, in (Kim 2004).…”
Section: Introductionmentioning
confidence: 99%